Interpretasi Hadis Qadhā’ Puasa Mayit menurut Metodologi Yusuf al-Qaradawi - Husna, Himmayatul; Khamim, Khamim (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2025)
This study explores the divergent interpretations among Muslim scholars regarding prophetic traditions (ḥadīths) associated with the legal obligation of qadhā’ (paying back the missed fasting) on behalf of deceased individuals. The disagreement emerges from the categorization of ritual worship (ʿibādah) into physical, financial, or combined acts, raising jurisprudential debates over whether such acts—especially fasting—can be fulfilled by legal proxy. Within Islamic legal discourse, some jurists argue that the guardian (walī) must perform the missed fasts of the deceased, while others opine that paying fidyah (compensatory feeding of the poor) is sufficient. These divergent views stem from differing hermeneutical readings of several ḥadīths, including those reported by ʿĀʾishah and Ibn ʿAbbās, which appear contradictory in literal interpretation. This research employs a qualitative methodology using a library-based (literature review) approach, analyzing hadith and fiqh texts across multiple legal schools (madhāhib). The interpretive framework of Yūsuf al-Qaradāwī is utilized to critically assess and reconcile these texts, incorporating key principles such as jamʿu al-aḥādīth (harmonization), tarjīḥ (preference of evidence), and asbāb al-wurūd (contextual background of narration). The study finds that al-Qaradāwī’s comprehensive approach to hadith interpretation allows for a more coherent understanding of scholarly disagreements and offers a rational foundation for legal rulings across schools. It concludes that methodological engagement with prophetic texts is essential in developing inclusive, adaptable, and well-reasoned Islamic legal judgments in the context of modern jurisprudential needs.